The micro cap investor : - Imperiale, Richard (John Wiley & Sons, 2005)
It’s unlikely that an investor could gain an information advantage over the legions of professional analysts that study large companies such as Microsoft or General Electric. However, it is probable that an investor can learn a great deal about a micro cap company that would usually go unnoticed by most Wall Street analysts. The Micro Cap Investor thoroughly explains the characteristics of the micro cap sector, and shows readers how to discover and exploit the information advantage embedded in these stocks.